Dependence of SpO2 signal noise on the pulse oximeter averaging time - Rafl-Huttova Veronika (Current Directions in Biomedical Engineering, 2021)
A model of the pulse oximeter, which consists of a transfer function between arterial and peripheral blood oxygen saturation (SpO2) and the noise typical for SpO2 records, is an important part of a mathematical model of oxygenation in neonates that is designed to test and compare different algorithms of oxygen control. The noise level in the SpO2 signal is affected by the averaging time setting of the pulse oximeter. This study aimed to characterize the noise level in the SpO2 signal at the set pulse oximeter averaging times of 2- 4, 8, and 16 seconds. We evaluated SpO2 records of 17 healthy volunteers who underwent a laboratory experiment in which they evoked different types of artifacts. The noise level in the SpO2 signal was characterized by two parameters, the deviation of SpO2 from the true value and the SpO2 time stability, defined as the interval during which the measured SpO2 value remained unchanged. Statistical properties of the noise level for the three averaging times were represented by normalized histograms of both the parameters and varied according to the type of artifact. With motion artifacts, the SpO2 readings deviated from the true value by more than ±2% SpO2 in 10%, 7%, or 5% of the measurements when the set averaging time was 2-4 s, 8 s, or 16 s. The length of the interval over which the SpO2 value remained unchanged was most frequently 2 seconds for all set averaging times. Implementation of the noise characteristics into the computer model of oxygenation in neonates will allow more faithful simulations of the output SpO2 signal that better match clinical observations.